Casualised academic staff and the lecturer-student relationship: Shame, (Im)permanence and (Il)legitimacy. Issue 4 (18th May 2020) - Read, Barbara; Leathwood, Carole
Abstract: This paper is based on findings from an email interview study with 20 academics (17 women, 3 men) in the UK on short-term, insecure or 'casualised' contracts. The paper focuses on their perceptions of the effect their contract status has on the lecturer/student relationship: particularly in regard to student perceptions of their legitimacy and status. Using a poststructuralist theoretical lens, we explore lecturers' concerns or anxieties as to whether they may be interpreted as less legitimate than permanent staff; and the emotional labour involved in the work done to 'cover' for the difficulties that a lecturer's contract status causes for the quality of their teaching content and organisation. We also explore the considerations of some participants to voluntarily 'disclose' their status to students and the possibilities of such acts as a form of resistance to dominant discourses of the legitimate academic.